INTEGRASI FRAMEWORK ISO 27001 DAN COBIT 2019 UNTUK SISTEM KEAMANAN INFORMASI PADA SMART TOURISM PT YoY MANAJEMEN INTERNASIONAL - Muhammad Nawir; Irfan AP; Farid Wajidi (Universitas Nusa Cendana, 2022)
Information technology that is growing rapidly becomes a very high threat to information systems. PT. YoY Management Internasional which will manage the location-based smart tourism application so that it is necessary to protect company information, in order to avoid interference and threats that can harm the company. In this study, an analysis of information technology (IT) governance was carried out using the COBIT 2019 framework, by aligning the company's strategies and goals into existing processes in COBIT 2019 which were then mapped into ISO 27001 for information security management. The purpose of this research is to manage information security using the COBIT 2019 framework and the ISO 27001:2013 standard. The research method used in this research is descriptive qualitative. The results obtained in this study are in the form of several recommendations for policies in managing information security in smart tourism applications in accordance with the COBIT 2019 and ISO 27001:2013 standards.